State of Stress in Annular Prestressed Plate Under Creep Conditions - Białkiewicz, J. (Engineering Transactions, 1985)
The solution of the problem of creep of an annular plate prestressed by a system of concentric cables is presented. The method of the solution is based on a double iterative algorithm. The problem of interaction of the cables and the influence of piane stress state on the state of bending of a plate have been solved by iterative methods.